The Prospect for Establishing of Islamic Cooperatives in Bunyu District, North Kalimantan - Fernanda, Ivan Aditya; Nurhasanah, Nining; Putri, Diana (Institut Agama Islam (IAI) SEBI, 2023)
This study aims to determine the prospects and potential for establishing sharia cooperatives in Bunyu District. The research method used is descriptive analysis to describe, present, or interpret literature data and interview results in the form of data presentation in the form of tables, graphs, pictures, and others, obtained from the Central Bureau of Statistics (BPS) Bulungan Regency and interviews using analysis TOWS (Treath, Opportunity, Weakness, Strength), IFAS and IFES. From the results of the analysis carried out resulted in several strategies that were very suitable for the conditions that existed in Bunyu District. The establishment of sharia cooperatives in Bunyu District has a very high opportunity to develop the economy of the people of Bunyu District, especially SMEs and fishermen. Plus support from the local government will also make it easier to prepare business capital with an easier loan system. Based on the results of research on the establishment of sharia cooperatives in Bunyu District, it has very good potential so that it can be concluded that the establishment of Islamic cooperatives in Bunyu District has a very high chance of developing the community's economy.